MEMAKNAI PENYUSUNAN DAN PELAPORAN AKUNTANSI PADA RUMAH SAKIT BLU (STUDI KASUS RSUP DR. MOHAMMAD HOESIN PALEMBANG) - Fardinant Adhitama (AKUNTABILITAS, 2015)
The arrangement and accounting reporting becomes an important component in a governance institution to assess the performance in a financial management which apply PSB (Public Service Board) accounting reporting is governed by laws and regulations in the field of state finances to run a sound business practice, PSB (Public Service Board ) carry out two systems with two standards for the preparation and reporting of accounting in financial governance GAAP (Generally Accepted Accounting Principles) as the standard in the preparation and reporting of accounting for financial reporting BLU (Public Service Board) accrual-based and GAS (Government Accounting Standards) as standard in preparation and accounting reporting of the government agencies with cash toward accrual basis. This research was conducted to understand and interpret how the implementation of the preparation and reporting of accounting PSB (Public Service Board) at Dr. Mohammad HoesinHospital Palembang then figure out what are the problems encountered in the preparation of accounting and reporting, and how the decisions taken by Dr. Mohammad HoesinHospital Palembang in following up the problems that arise, this study is a qualitative research paradigm interpratif research with case study approach. The object of this research is part of the accounting department of Dr. Mohammad Hoesin Palembang with speakers Head of financial accounting along with the associated staff. Data analysis is done with data reduction, understanding and interpretation. The results of the study describes howthe process of preparation and accounting reporting that occurred at Dr. Mohammad Hoesin Hospital Palembang as the implementing agency of PSB (Public Service Board), researchers also found a lot of problems that arise in the preparation and reporting of accounting process on PSB (Public Service Board) governance of Dr. Mohammad Hoesin Hospital Palembang, then the results of this study explain the decisions taken by rational choice theory. Suggestion that is given in this study is that the central government may revise the regulation in the financial governance of PSB (Public Service Board) particularly regardingGeneralServices AgencyHospital.